Challenges in Diagnostics and Management of Atypical Hemolytic Uremic Syndrome Associated with Acute Intestinal Infection in Adolescent: Clinical Case - Tatiana Yu. Eryushova; Alfiia I. Aminova; Sofiia A. Lakhova; Zarnigar F. Gumbatova; Murat K. Astamirov; Olga Yu. Brunova ("Paediatrician" Publishers LLC, 2020)
Background. Acute intestinal infections (AII) caused by Shiga-like toxin-producing Escherichia coli and accompanied by hemolytic uremic syndrome (HUS) development are characterized by rapid progression and poor prognosis. Bloody diarrhea (hemorrhagic colitis) requires timely medical treatment both at young age and at adolescence. The severe course of HUS affected by AII caused by enterohaemorrhagic Escherichia coli requires additional medical attention and timely renal replacement therapy (hemodialysis).Clinical Case Description. The description and analysis of the severe course of HUS affected by AII in 14 years old adolescent girl is presented. There were some difficulties during diagnostics and thus the pathogenetic therapy onset was delayed. Differential diagnosis between typical and atypical HUS was performed. The disease was characterized by rapid progression of acute kidney injury, cerebrovascular disease and ischemia, multiple organ dysfunction syndrome and disseminated intravascular coagulation resulting in fatal case.Conclusion. Atypical HUS is the most frequent cause of multiple organ dysfunction syndrome alongside with acute kidney injury. The challenges of early diagnostics of atypical GUS in childhood are not fully solved nowadays and require additional attention of pediatricians. The clinical case of atypical GUS complicated by intestinal infection caused by enterohaemorrhagic Escherichia coli is described in this article. The severity of the disease course was due to the early manifestation of extrarenal symptoms and multiple organ failure.